2003
DOI: 10.1189/jlb.0402163
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of galectins in myeloid differentiation into three different lineages

Abstract: Little is known about the roles of galectins, a family of beta-galactoside-binding lectins, in myeloid cell differentiation. In the present experiments, we used HL-60 cells as a model of myeloid cell differentiation. The HL-60 cells were differentiated into eosinophil-, monocyte-, and neutrophil-like cells by coculture with sodium butyrate under a mild alkaline condition, phorbol 12-myristate 13-acetate, and dimethyl sulfoxide, respectively. Thus, the expression of galectins in HL-60 cells during differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…Gal are also implicated in myeloid differentiation (17). We have thus shown that Gal-9 expression gradually decreases, whereas Gal-10 expression increases during eosinophil differentiation and that Gal-9 expression decreases, whereas Gal-3 expression increases during monocyte differentiation.…”
Section: G Alectins (Gal)mentioning
confidence: 78%
“…Gal are also implicated in myeloid differentiation (17). We have thus shown that Gal-9 expression gradually decreases, whereas Gal-10 expression increases during eosinophil differentiation and that Gal-9 expression decreases, whereas Gal-3 expression increases during monocyte differentiation.…”
Section: G Alectins (Gal)mentioning
confidence: 78%
“…The cells' reactivity was particularly strong toward members of the proto-type subfamily at the late stages of the cell death program. Despite sharing sequence homology, their expression and activity patterns, for example, in vitro and in vivo or with respect to caspase activation in human T cell apoptosis, differ so that they should not be considered to exert fully overlapping functions (46)(47)(48)(49). Having herewith identified human galectins as sensors for apoptosis/necrosis-associated cell surface changes, the next step will be to define a functional significance of this interplay.…”
Section: Discussionmentioning
confidence: 99%
“…10 Galectin-3 is a differentiation marker for human monocytes or promyelocytic cell line HL-60, which can be differentiated into macrophage-like cells by phorbol ester treatment. 11 Galectin-3 is considered as macrophage activation marker as it is overexpressed in phagocytic macrophages. 12 Galectin-3 level is also increased in myelin-activated microglia and macrophages.…”
Section: Introductionmentioning
confidence: 99%